SAT0551 Leg ulcers in behcet's syndrome: an observational survey in 24 patients. (12th June 2018) - Ozguler, Y.; Kutlubay, Z.; Dikici, A.S.; Melikoglu, M.; Mat, C.; Yazici, H.; Seyahi, E.
Abstract : Background: Formal experience with leg ulcers in Behçet's syndrome (BS) is limited. It is a rare complication that can be seen during the course of mainly pts with the post-thrombotic syndrome. They can be difficult to manage and may cause disability leading to unemployment and severe impairment in quality of life. Objectives: In this observational survey, we aimed to describe clinical characteristics of pts with leg ulcers. Methods: A total of 24 pts (23 M/1 F) that were seen at our multidisciplinary BS clinic between May 2016-Jan 2018 were evaluated with the help of a standardised questionnaire. Venous Doppler US and if necessary abdominal CT were used to evaluate localization of venous involvement. Biopsies were done if needed. Medical and other interventional treatments were recorded. Results: The mean age at disease onset was 27.5±7.1 years. The median duration between the disease onset and ulcer development was 4.0 [2.5–11.5] years. The median follow-up was 7.8 [IQR: 2.9–14.2] years. Eleven (46%) were unemployed due to the leg ulcer. Venous involvement was present in 20 pts (83%). Lower extremity vein thrombosis was shown in all these 20 pts. It was mostly bilateral (15/20). Femoral veins were the most commonly involved (18/20), followed by popliteal veins (14/20), v. saphena magna or v. saphena parva (7/20), iliac veins or inferior vena cava (8/20). The same 9/20 pts had other large vessel involvement such as pulmonary artery (n=5) or dural sinus thrombosis (n=3). Four pts did not have any venous thrombosis or insufficiency. Histopathologic studies could be done in 3 and showed necrotizing vasculitis in 2 and venous stasis in the 3rd. Twelve pts (50%) had solitary ulcers and 12 had 2 or more. We observed a total of 34 ulcers in 24 pts. They were mostly found around the medial malleolus (15/34) and anterior surface of the tibia (14/34). Five pts had leg ulcers at unusual places such as lateral malleolus (n=2), popliteal fossa (n=1) and posterior surface of the tibia (n=2). Immunosuppressive agents including azathioprine, cyclophosphamide, interferon alpha, infliximab, and corticosteroids were used. Bed rest was advised to almost all. Iloprost infusions were given in 13 (54%) for a median duration of 6 mo. Additionally, larvae of Lucilia sericata were tried in 9 pts. Skin graft insertion was used in 2 pts, however, was successful in 1. We observed that in 11 (46%) pts 17 ulcers healed in median 24 mo [IQR:9–78]. In the remaining 13 (54%) pts 17 ulcers stayed as unhealed for a median 7 years [IQR:5–11], despite all interventions and medical treatment. We saw the mean age at BS onset was significantly younger (24.4±5.4 vs 30.4±7.3 years; p<0.05) and the median time between disease onset and ulcer development was significantly shorter (3 [IQR:1–4.5] vs 10 [IQR:4–14 years, p<0.05] in pts with healed ulcers compared to those with unhealed ulcers. There were no apparent associations with the type of management and the severity of venous involvement. Conclusions: Leg ulcer develops mainly due to venous disease in the lower extremities. Peripheral arterial occlusive disease seems to be rarely involved. It may cause unemployment in 46% and be resistant to treatment in 54% of the cases. Ulcers that appear early during the disease course heal faster and is more responsive to treatment. Disclosure of Interest: None declared